Penyuluhan Perilaku Hidup Bersih Dan Sehat Di SDN 16 Air Tawar Padang Utara - Yuliza Birman; Rosmaini; Fikri Wahyuda Ismail; Shyntia Peratami Putri; Nadilla Nurrifdah; Puja Wanandri; Latifah Azzahra; Rezy Saputra; Dwita Widya Kartika (CV. Multi Kreasi Media, 2023)
Clean and healthy life behavior, often abbreviated as PHBS, is all behavior as a form of embodiment of a healthy life orientation in individual, family and community culture, which aims to improve, maintain and protect one's health physically, mentally, spiritually and socially. One of the most important PHBS is PHBS in schools. PHBS in schools is an activity to empower students, teachers and the school community to want to adopt a healthy lifestyle to create healthy schools. The benefits of PHBS in schools are able to create a clean and healthy environment, improve the teaching and learning process and students, teachers and the school community become healthy. implementation of PHBS in schools includes washing hands with soap, consuming healthy snacks, using clean and healthy latrines, exercising regularly, eradicating mosquito larvae, not smoking in the school environment, disposing of trash in its place, and, doing community service with school residents to creating a healthy environment. Health promotion regarding PHBS was carried out at SDN 16 Air Tawar, North Padang District, Padang City on Saturday, December 3, 2022 with a total of 46 participants consisting of grade 3 and 4 students.